For The Sake of Survival: Illegal Gold Mining Exploitation Crimes from Environmental Fiqh in South Aceh Regency - Yuhasnibar Syah; Nurulbahiah binti Awang; Iskandar Iskandar; Rahul Husni (Islamic Criminal Law Department, Faculty of Sharia and Law, UIN Ar-Raniry, 2024)
Criminal acts of illegal mining in East Labuhahaji District, South Aceh, continue to be carried out by the community without paying attention to the negative impacts on the surrounding environment, which can result in losses for the benefit of the community. This article aims to analyze the factors and impacts of illegal gold mining on the environment of the people of Labuhan Haji Timur District, South Aceh Regency, in terms of environmental fiqh. Data was obtained through interviews and analyzed critically. The research results show that the factors causing people to carry out illegal gold mining in East Labuhanhaji District are low economic life and community education, minimal socialization regarding mining prohibitions, and minimal public awareness of religious values regarding environmental damage. Illegal gold mining has a negative impact in the form of deforestation, making it prone to flooding and damage to plantation land. Judging from environmental fiqh, the criminal act of illegal gold mining in Labuhan Haji Timur District, South Aceh Regency, is an act of jihad that is contrary to Islamic law because it hurts environmental damage and the benefit of the community at large. Therefore, in Islamic law, illegal gold mining can be subject to sanctions in the form of ta'zir.